Syndecan-1-Induced ECM Fiber Alignment Requires Integrin αvβ3 and Syndecan-1 Ectodomain and Heparan Sulfate Chains. - Ning Yang; Andreas Friedl (PLoS ONE, 2016)
Expression of the cell surface proteoglycan syndecan-1 (Sdc1) is frequently induced in stromal fibroblasts of invasive breast carcinomas. We have recently identified a correlation between stromal Sdc1 expression and extracellular matrix (ECM) fiber alignment, both in vitro and in vivo. ECMs derived from Sdc1-positive human mammary fibroblasts (HMF) showed an aligned fiber architecture, which contrasted markedly with the more random fiber arrangement in the ECM produced by Sdc1-negative HMFs. We further demonstrated that aligned fiber architecture promotes the directional migration and invasion of breast carcinoma cells. To decipher the molecular mechanisms governing the formation of an aligned, invasion-permissive ECM, a series of Sdc1 mutants was introduced into HMF. We found that both the ectodomain and heparan sulfate chains of Sdc1 were required for full activity of Sdc1 in regulating ECM alignment, while transmembrane and cytoplasmic domains were dispensable. Sdc1 regulates the activities of several integrins via its ectodomain. Integrins are key players in the assembly of fibronectin-rich ECM. In addition, integrins are capable of regulating cell morphology and cell shape and orientation may affect ECM architecture. Therefore, we investigated the role of integrins in Sdc1-mediated ECM fiber alignment. Sdc1-overexpressing HMF gained an enhanced spindle-shaped morphology when cultured in an overconfluent state under conditions permissive for ECM production, which was partially reversed by siRNA-mediated silencing of β3 integrin expression. Moreover, suppression of αvβ3 integrin activity by a function-blocking antibody or β3 knockdown largely abolished the aligned ECM fiber architecture and consequently the invasion-permissive properties of the ECM induced by Sdc1. The results suggest that Sdc1 may modulate fibronectin fibrillogenesis and/or alter cell morphology during ECM production through αvβ3 integrin, thereby mediating ECM fiber alignment. Understanding the mechanisms governing ECM organization may lead to the development of novel stroma-targeted therapy for breast cancer, aiming at converting an invasion-permissive to an invasion-restrictive microenvironment.